Penguatan Pemahaman Moderasi Beragama Mahasiswa Teknik Komputer melalui Project-Based Learning Berbasis Kampanye Digital - Baso Ilyas (Lembaga Yasin AlSys, 2026)
The rapid development of the internet and social media has increased young people’s exposure to various forms of religious information, including intolerant content and exclusive religious narratives in digital spaces. This condition requires the strengthening of religious moderation that is appropriate to the characteristics of students in engineering-related disciplines, who have a high intensity of digital interaction. This study aims to evaluate the contribution of Project-Based Learning (PjBL) based on digital visual campaigns to Computer Engineering students’ understanding and interpretation of religious moderation. This study used a mixed-methods approach with a convergent parallel design. The research participants consisted of 45 students selected through purposive sampling. Data were collected through Likert-scale questionnaires and reflective essays after the entire project sequence had been completed. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed through thematic analysis. The results showed that students gave positive responses to the implementation of PjBL and the use of digital visual campaigns in religious moderation learning. A total of 51.1% of respondents strongly agreed and 48.9% agreed that visual media were effective in conveying messages of peace. Students’ reflections showed that intolerance was understood not only as a matter of differences in belief but also as related to disinformation, hate speech, and low digital literacy. Students also interpreted the concept of ummatan wasathan as an encouragement to be fair, critical, and not easily provoked in responding to information on social media. However, 26.7% of respondents gave neutral responses regarding the effectiveness of PjBL compared with the lecture method, indicating that support through conceptual explanation remains necessary in the learning process. These findings show that PjBL based on digital visual campaigns contributes positively to helping students connect the values of religious moderation with religious issues in digital spaces. The implications of this study affirm the importance of integrating digital religious literacy and contextual learning activities into Islamic Religious Education in higher education.